Extraction & Purification of Plasmid from Some Spices of E. coli in Different Ways - Taha, Abdullah M.; Hammed, Zainab Noori; Kareem, Alaa M. (Journal for Research in Applied Sciences and Biotechnology, 2023)
This study involved the use of multiple methods to separate plasmids from bacterial cell DNA for some isolates of pathogenic E. coli through several steps, starting with the analysis of the bacterial cell using lysozymes to remove the outer wall, followed by centrifugation to isolate plasmids found in the solution from the rest of the proteins and other forms of DNA. Many sequential methods were used to separate plasmids. The first method used was the basal denaturation sodium hydroxide-based, which led to the denaturation of the chromosomal DNA without affecting the plasmid DNA, followed by the addition of sodium acetate, which led to the preservation of the shape and structure of the plasmid DNA. Second, using cesium chloride gradient density to isolate the protein cell components and the rest of the DNA forms. The different densities of these components led to the appearance of sequential bundles depending on their different molecular weights. Ethidium bromide, which gave the plasmid bundles a fluorescent dye, was added using ultraviolet rays. The last purification method was using the boiling method using a water bath. Plasmid samples extracted from the previous methods were taken to perform the purification and separation process using the high electrophoresis method. Akarose gel was used to separate the high molecular weight protein fragments. Standard proteins and plasmids were migrated to determine the volumes of purified plasmids.